EAA and Afghanistan: Nine Years Ago - EAA Editorial Office (Education About Asia, 2021)
Two authors with impressive expertise on Afghanistan and the ability to write for educated lay people as well as high school and university students were each solicited to write separate essays entitled “What History Can Teach Us About Contemporary Afghanistan.” Those teachers who are looking for well-done, concise, and high quality contextual articles for themselves and their students that provide some foundation to think more deeply about unfolding events in Afghanistan that will potentially affect not only Afghanistan and the US, but much of the world, are highly encouraged to read the essays by Thomas Barfield and Thomas Gouttierre.
Keywords: Afghanistan; Conflict Studies; History; International Relations; Political Science; South Asia